2015
DOI: 10.1149/2.0741512jes
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Prop-1-ene-1,3-Sultone and Vinylene Carbonate in LiNi1/3Mn1/3Co1/3O2/Graphite Pouch Cells: Electrochemical, GC-MS and XPS Analysis

Abstract: The role of prop-1-ene-1,3-sultone (PES) used alone or in combination with vinylene carbonate (VC) in LiNi1/3Mn1/3Co1/3O2(NMC)/graphite pouch cells was studied by correlating data from differential capacity (dQ/dV) analysis, gas chromatography/mass spectroscopy (GC−MS), ultrahigh precision coulometry, storage experiments and X-ray photoelectron spectroscopy. VC formed more stable and protective SEI films at both graphite and NMC surfaces due to the formation of a polymer of VC. For PES-containing electrolytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 57 publications
6
53
0
Order By: Relevance
“…48,51,52,67,75,76 It is then possible that the transesterification of EMC occurs during the sudden failure of the LCO/Si:gr cells because of the absence of FEC. However FEC could, in principle, prevent the transesterification of EMC in two different ways.…”
Section: Resultsmentioning
confidence: 99%
“…48,51,52,67,75,76 It is then possible that the transesterification of EMC occurs during the sudden failure of the LCO/Si:gr cells because of the absence of FEC. However FEC could, in principle, prevent the transesterification of EMC in two different ways.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically speaking, functional additives with a higher HOMO energy than carbonate solvents will be preferentially oxidized to modify the cathode SEI layer, while those with a lower LUMO energy than carbonate solvents will be preferentially reduced to modify the anode SEI layer. [31,32,[54][55][56][57][58][59] The most typical electrochemical reduction species of these organic sulfur-containing compounds are passivating ROSO 2 Li and Li 2 SO 3 , which can facilitate lithium ion diffusion through SEI layer and prevent the excessive reductive decomposition of carbonate solvents (such as propylene carbonate). [35,[48][49][50][51][52][53] With a higher HOMO energy relative to carbonate solvents, TMSP easily undergoes electrochemi cal oxidations and promotes the formation of a protective SEI layer on the surface of high-voltage cathode materials (such as LiNi 0.5 Mn 1.5 O 4 , LiNi 0.5 Co 0.2 Mn 0.3 O 2 , overlithiated layered oxide).…”
mentioning
confidence: 99%
“…More recently, using XPS experiments, Madec et al 27 showed that in NMC/graphite pouch cells balanced for 4.2 V, PES forms more protective and stable SEI films at both graphite and NMC surfaces which might explain the improved electrochemical * Electrochemical Society Student Member. * * Electrochemical Society Fellow.…”
mentioning
confidence: 99%
“…More recently, using XPS experiments, Madec et al 27 showed that in NMC/graphite pouch cells balanced for 4.2 V, PES forms more protective and stable SEI films at both graphite and NMC surfaces which might explain the improved electrochemical performance as well as the lower production of gas observed with PES compared to control electrolyte. They attributed these results to the preferential reaction of PES at both graphite and NMC surfaces that led to an additional contribution of sulfite species and substantially less LiF compared to control electrolyte.…”
mentioning
confidence: 99%